The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
CALL Communities and Culture – Short Papers From EUROCALL 2016 2016
DOI: 10.14705/rpnet.2016.eurocall2016.537
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of text-to-speech synthesizers in the foreign language classroom: learners’ perceptions

Abstract: As stated in Cardoso, Smith, and Garcia Fuentes (2015), second language researchers and practitioners have explored the pedagogical capabilities of Text-To-Speech synthesizers (TTS) for their potential to enhance the acquisition of writing (e.g. Kirstein, 2006), vocabulary and reading (e.g. Proctor, Dalton, & Grisham, 2007), and pronunciation (e.g. Cardoso, Collins, & White, 2012). Despite their demonstrated effectiveness, there is a need for up-to-date formal evaluations of TTS systems, specifically for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Research on the quality of TTS has led Google to assert that deep neural network (DNN) technology already produces near-human speech [56]. As mentioned earlier in the introduction, despite a certain amount of controversy concerning the pedagogical use of TTS systems in L2 teaching, there is empirical evidence that supports its applicability [57]- [59].…”
Section: A Speech Technologies For Pronunciation Trainingmentioning
confidence: 99%
“…Research on the quality of TTS has led Google to assert that deep neural network (DNN) technology already produces near-human speech [56]. As mentioned earlier in the introduction, despite a certain amount of controversy concerning the pedagogical use of TTS systems in L2 teaching, there is empirical evidence that supports its applicability [57]- [59].…”
Section: A Speech Technologies For Pronunciation Trainingmentioning
confidence: 99%
“…In particular, ASR-based CAPT systems present several advantages, such as dynamic evaluation, more intensive practice, immediate-automated feedback, anxiety-free context, individualized feedback, and opportunities for repair (Neri et al 2002(Neri et al , 2006. Even though old TTS systems generated a great deal of controversy when used as a pedagogical tool, recent research in speech synthesis has reported some benefits in terms of naturalness, comprehensibility, accuracy, and intelligibility (Smith et al 2015 andBione et al 2016).…”
Section: Advantages Of the Toolmentioning
confidence: 99%
“…In the context of language acquisition, the quality of the synthesised speech may be of importance, as (young) learners have been shown to attend to non-verbal cues present in the speech signal when presented with a novel language (e.g., Dominey and Dodane, 2004). Although the effects of speech synthesis quality on learners' perceptions have previously been studied for computerassisted language learning (e.g., Bione et al, 2016;Handley, 2009;Kang et al, 2008), whether poor quality speech synthesis impedes the efficacy of language acquisition has not been unequivocally established.…”
Section: Speech Synthesismentioning
confidence: 99%